The health/disease transition process in chronic kidney disease patients: Contributions to nursing care - Francieli Aparecida de Oliveira; Ana Raquel Lima Peralva de Almeida; Thaciane Alves Mota; Joice Requião Costa; Magna Santos Andrade; Rudval Souza da Silva
Abstract Objective: To identify the facilitating and hindering conditions of the health/disease transition process in a group of patients with Chronic Kidney Disease undergoing hemodialysis treatment based on the theoretical framework of the Transition Theory. Method: A descriptive study implementing a qualitative approach. Data collection occurred through semi-structured interviews conducted between March and April 2018. The Content Analysis Technique was used for analysis and discussion as a methodological framework and the explanatory model of the Transition Theory as a theoretical framework. Results: Twenty-five (25) patients participated in the study. The conditioning factors of the transition process were identified and organized into three thematic categories: Personal conditioning factors in the transition process; Community conditioning factors in the transition process; and Social conditioning factors in the transition process. Conclusion: A predominance of hindering conditioning factors was evidenced in the personal dimension, while facilitating conditioning factors were shown in relation to the community dimension, and finally the conditioning factors were equal regarding the social dimension.